Heterosis and combining ability estimates for the total number of eggs laid per female in silkworm, Bombyx mori L. (University Journal of Zoology, Rajshahi University, 2012)
Heterosis and combining ability for total number of eggs laid per female silkworm Bombyx mori L were investigated in a six parent diallel crossing programme in four rearing seasons. Magnitude of heterosis varied from seasons to season and was not consistent over characters. Effect of season was important in the expression of genetic variances and other parameters studied. Considerable amount to heterosis was obtained in the crosses where parents Nistari Oval (G), BSRI-98 and BV-High were involved. Parental performance as judged by general combining ability quantities indicated that BSRI-98 was the best general combining parent in all the rearing seasons. The variance due to the specific combing ability (?2 sca) was higher than the general combining ability (?2gca) in all seasons, indicating the preponderance of non-additive gene action in inheritance of that trait. Majority of the crosses showing significant sca effects had either one or both the parents were good general combiners. Thus the combining ability of parents may be considered as a reliable guide in the prediction of the yield potential of those crosses. The crosses Nistari Oval (G)×BSRI-98, Nistari×BSRI-98 and BSRI-95× Nan Nung7B are recommended for the commercial exploitation of heterosis as an important egg producing breeds in majority of the rearing seasons.DOI: http://dx.doi.org/10.3329/ujzru.v30.10754 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 55-59